2017
DOI: 10.3390/ijgi6090287
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Correction to Landsat Imagery through Slope Classification by Applying the SCS + C Method in Mountainous Forest Areas

Abstract: The aim of the topographic normalization of remotely sensed imagery is to reduce reflectance variability caused by steep terrain and thus improve further processing of images. A process of topographic correction was applied to Landsat imagery in a mountainous forest area in the south of Mexico. The method used was the Sun Canopy Sensor + C correction (SCS + C) where the C parameter was differently determined according to a classification of the topographic slopes of the studied area in nine classes for each ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…A strong and statistically significant relationship between local illumination and pixel value has been reported in the literature (Kobayashi and Sanga-Ngoie 2008, Soenen et al 2008, Wu et al 2008, Mishra et al 2009, Zhang and Gao 2011, Vázquez-Jiménez et al 2017 and is confirmed in this study. The initial objective of this research was to identify which topographic algorithm Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A strong and statistically significant relationship between local illumination and pixel value has been reported in the literature (Kobayashi and Sanga-Ngoie 2008, Soenen et al 2008, Wu et al 2008, Mishra et al 2009, Zhang and Gao 2011, Vázquez-Jiménez et al 2017 and is confirmed in this study. The initial objective of this research was to identify which topographic algorithm Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Several topographic correction methods require the satellite imagery to be atmospherically corrected (surface reflectance) (Richter 1997, Riaño et al 2003, Vanonckelen et al 2014, Pimple et al 2017, Vázquez-Jiménez et al 2017, Phiri et al 2018. However, the use of top-of-atmosphere (TOA) reflectance is also fairly common (Richter et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The C parameter used in the topographic correction to improve the correction by moderating the overcorrection of dimly illuminated pixels [60] was determined by linear regressions between the values of illumination and reflectance, according to a classification of the topographic slopes of the studied area [61].…”
Section: Topographic Normalizationmentioning
confidence: 99%
“…Some improved models have been developed to reduce the topographic effects for the regions with complex terrains, such as the sun-canopy-sensor + C (SCSC) model [30,35] and the rotation correction model [36]. Although these models can achieve sound corrections, their performance relies very much on the experimental parameters fitted by the pixel reflectance and the cosine of solar incident angles, such as the factor c for C-Correction (CC) models, factor a for rotation correction models, and constant k for MIN models.…”
Section: Introductionmentioning
confidence: 99%